Collaborative Governance Model in Poverty Alleviation in the Tanimbar Islands Regency: A Study of Regional Policy Implementation - Edoardus Koisin; Agus Sukristyanto; Ayun Maduwinarti (International Research and Development for Human Beings (IRDH), 2024)
This study aims to analyze the application of the collaborative governance model in poverty alleviation in the Tanimbar Islands Regency, Maluku Province. The collaborative governance model involves various stakeholders, including local government, the private sector, communities, academia, and media, collaborating effectively and efficiently to address poverty issues. This research employs a qualitative approach, utilizing data collection techniques such as in-depth interviews, observations, and documentation studies. The findings indicate that the implementation of collaborative governance in Tanimbar is underway but not optimal regarding collaboration among stakeholders in poverty alleviation efforts, particularly in sustainable community economic empowerment programs. Based on these findings, recommendations are provided to the local government to enhance poverty alleviation efforts in the Tanimbar Islands Regency.